Software Requirement Analysis and Design: Object-oriented approach with UML - Abd Ghani, M. K.; Sulaiman, S (Penerbit UTeM, 2011)
This book is aimed primarily as lab sessions for software requirement and design. It focuses on the basic concepts of object-oriented software analysis and design using Unified Modeling Language (UML). The chapters of this lab module are arranged based on the phase by phase in software development process beginning with project planning, requirement analysis, analysis and design, testing and implementation. Upon completion of this module, the students would have understood the fundamentals of object-oriented software analysis and design using UML and know how to develop the software from scratch to the final product. The first edition of this lab module acts as a baseline for the future improvements. We welcome any response and constructive comments from students, academicians and anyone who is interested with this module.